(untitled) (Research, Society and Development, 2021)
The present work aims to review the literature analyzing instruments in mechanized kinematics, emphasizing two reciprocating instrumentation systems (Reciproc Blue, WaveOne Gold), and to identify their main characteristics and advantages compared to manual and rotary instrumentation. A bibliographic survey was carried out in the online databases of PubMed, SciELO, Lilacs, Science Direct, scientific articles of systematic review/meta-analysis, clinical cases, experimental studies in vitro/in vivo, and prospective and retrospective researches were included. With delimitation of specific period, from 2008 to 2021, within the proposed theme, which addressed the mechanized NiTi instruments, with an emphasis on the Reciproc Blue and WaveOne Gold systems. Following the inclusion criteria, the available abstracts were read and 22 articles that were part of this study were identified. Thus, it is concluded that there is no perfect system, each one has its advantages and disadvantages when compared to its competitors. Therefore, it is essential to understand how the system works, and master its use to obtain better results in endodontic therapy.